The cognitive and educational importance of the academic teacher for developing the applied skills of third-stage female students in the subject of teaching methods from their point of view - Yasir Hussein Khudhair,; Abdullah Ghazi Hamdan,; Saad Abbas Fadhil, (Eximia, 2024)
The research aimed to prepare a measure of the importance of enlightenment, academic education, and applied skills for third-stage female students, including teaching methods from their point of view/College of Education and Sports Sciences/University of Baghdad/Al-Jadriyah. The researchers used descriptive description in the comprehensive research procedures, an appropriate methodology in achieving the research objectives, sufficient for interpretations, how important is the academic teacher’s knowledge of teaching methods for student learning, what are the roles that the learners have acquired from the academic teacher. The scale of importance and horror consists of 15 items. The research population includes female students of the third stage/College of Education, Fitness and Sports Sciences, numbering (135) students. Attractive artistic drawings were chosen in proportion to 48%. The researchers concluded that the educational and cognitive importance of the academic teacher for developing applied skills for female students is considered the main focus for learners, especially for third-year female students, as she is the link through which what has been learned at this stage is linked and refined in the next stage of the educational process for female students. The researchers recommend benefiting from the academic teacher for the subject. Teaching methods in holding workshops and lectures for all educational levels, and emphasizing the importance of the subject of teaching methods for learners because it is the jewel that is acquired during the four years of study.